Analisis Tata Kelola Dana Desa Berbasis Good Governance dalam Pembangunan dan Pemberdayaan Masyarakat Desa Pepelegi, Kabupaten Sidoarjo (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
The purpose of this study is to examine the application of good governance principles in the management of Village Funds in Pepelegi Village, Waru District, Sidoarjo Regency, and to assess its compliance with Home Affairs Ministerial Regulation Number 20 of 2018, using qualitative descriptive methods in the form of interviews, observations, and document analysis. The informants used in this study were community representatives, BPD members, the Village Secretary, the Head of Finance, and the Head of Planning. The research findings show that Village Funds have been managed according to the provisions (starting from planning, implementation, administration, reporting, and accountability). During the planning stage, village meetings were conducted in a participatory manner, and planning documents were prepared following the established standards. The implementation stage relied on a self-management system (swakelola), using locally sourced materials and involving community participation through collective work (gotong royong). In the administrative stage, financial records were properly maintained using the Village General Cash Book and supporting documents. Reporting was completed on schedule by village officials, while accountability reports were submitted to the subdistrict (Camat) and made accessible to the community. Overall, the management of Village Funds in Pepelegi Village reflects adherence to accountability, transparency, and community participation principles and complies with the provisions outlined in Permendagri No. 20 of 2018.